Early detection and rehabilitation technologies for dementia : neuroscience and biomedical applications - Wu, Jinglong, 1958- (Hershey, PA : Medical Information Science Reference)
"This book provides a comprehensive collection for experts in the Neuroscience and Biomedical technology fields, outlining various concepts from cognitive neuroscience and dementia to neural technology and rehabilitation"--Provided by publisher.